Wood pellet supply chain costs – A review and cost optimization analysis. (February 2020) - Visser, L.; Hoefnagels, R.; Junginger, M.
Abstract: Wood pellet-based electricity production has the potential to increasingly contribute to the achievement of climate targets. A reduction of supply chain costs could contribute to increased utilization of pellets. Existing literature on pellet costs was reviewed to explicate cost differences, focusing on the impact of supply chain design. This was combined with a techno-economic analysis of the impact of different design variables on cost components, including feedstock type, production location and pellet plant size. The results of this study show that variation in literature can only be partly attributed to design differences, with large remaining uncertainty. The cost reduction potential of optimization strategies was found to be limited. Different supply chain design approaches result in trade-offs between cost components. Increasing the size of pellet plants was calculated to result in decreased pelletizing and shipping costs, but at the same time leads to increased costs for feedstock procurement and transport. Supply chain costs are highly dependent on specific supply chain conditions, including the regional availability of feedstock, and results varied for different pellet plant locations analyzed within the US. The average calculated costs for a 500 kt/a pellet plant amount to 136 €2017 /t pellets, compared to 143 €2017 /t pellets for a 50 kt/a pellet plant. The most prominent components across the entire chain are feedstock costs and pelletizing operating costs, including additional feedstock use for drying. The data used in this study can be found in the supplementary database. Highlights: Wood pellet cost variation in literature can only partly be attributed to supply chain design differences. Supply chain design optimization results in a trade-off between different cost components. Increased pellet plant size results in decreased pelletizing and shipping costs and increased feedstock and transport costs. Feedstock costs and pellet plant operating costs are the most expensive parts of the supply chain. Average calculated costs for a 500 kt/a and 50 kt/a pellet plant amount to 136 and 143 €2017 /t pellets, respectively.